Comparison of Psychiatric Morbidities among Pupils in Traditional Almajiri and Almajiri-Integrated Model Schools in Sokoto Metropolis, Northwest Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:Almajiri pupils are a form of street children, belonging to children on the street. Streetism is associated with a lot of physical and social stress.Aim:This study examined the prevalence of psychiatric morbidity and sociodemographic factors among pupils in traditional Almajiri (Tsangaya) and Almajiri Integrated Model Schools (AIMS) in Sokoto metropolis, northwest Nigeria.Methods and Materials:Pupils within the ages of 6–17 years participated in this cross-sectional comparative study. Through a multistage sampling technique, 96 pupils from each of Tsangaya and AIMS were selected as an equal sample. The Kiddies Schedule for Affective Disorders and Schizophrenia, Present and Lifetime (K-SADS-PL), and sociodemographic variables were assessed. The Statistical Package for Social Science version 21 software for windows was used to analyze the data.Results:We studied 192 all male pupils, whose mean age and standard deviations were 13.01 ± 2.30 and 12.91 ± 2.15 years in Tsangaya and AIMS, respectively. Overall, the prevalence of psychiatric morbidities was 27.6%, in a proportion of 67.9% to 32.1% in Tsangaya and AIMS, respectively. The common psychiatric disorders in this study were depression, enuresis, and posttraumatic stress disorder.Conclusion:Tsangaya pupils experience more psychiatric morbidity compared to their counterparts in AIMS. Neurotic disorders were found to be more prevalent among them. More AIMS should be created to reduce the prevalence of psychiatric morbidity among the vulnerable children in Tsangaya.